ORGANIZING E-LEARNING OF PHYSICS - EDUCATIONAL ACTIVITIES IN OUT-OF-SCHOOL HOURS - A. Voronkin (Kherson State University, 2012)
Experience of organizing pedagogical experiment - an open distance course «Introduction in acoustics» is analyzed in this paper.